Pelayanan, Ketersediaan Mempengaruhi Lolayitas Melalui Kepuasan dan Kepercayaan (Study: Bengkel Kendaraan Roda Dua Poen di Kotamadya Yogyakarta) - Wendri Rusli (JURNAL MANAJEMEN, 2011)
Marketing for customer loyalty is unchalenged and mastering customer needs to be improved at long term. This research is to test element which has relationship with customer loyalty that is: availability of spare part, trust, satisfaction. There are 120 respondents has interviewed and the data analyzed using Structural Equation Modelling (SEM). Result show that service are positively related to satisfaction, spare part availability positively related to customer satisfaction and customer satisfaction are positively related to loyalty. Service positively related to trust, spare part availability are positively related to trust and customer loyalty . Managerial implication suggest to improved satisfaction, trust to increase service quality and availability of spare part. Key word: Service, availability of spare part, satisfaction, trust and customer loyalty.